Collaborative governance for responsible innovation in the context of sharing economy: Studies on the shared bicycle sector in China - Zheng Liu; Lei Ma; Tianyu Huang; Hengzhao Tang (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The shared bicycle sector is a new type of rental business that combines the sharing economy with technology platforms. With its convenience, efficiency and low cost, the business has become popular in China. However, alongside the development of the shared bicycle industry, the increasing number of products, lack of governance, distrust between companies and users cause problems due to irresponsibility. This paper focuses on the governance of the shared bicycle sector, with the aim of achieving responsible innovation through a collaboration among stakeholders. Through case studies on two cities in China, the paper identifies government policies in the traditional context of hard-law regulation, and in the new context of multi-collaborative governance. The roles of government, industry and society are specified in the innovation ecosystem and are linked with the key dimensions of responsible innovation, anticipation, reflectiveness, inclusiveness and responsiveness. Based on the findings, a model is proposed, suggesting the new government roles of alliance facilitator and platform coordinator. Finally, our recommendations for the improvement of the shared bicycle sector are made and areas for future research are discussed.
Keywords: 650; collaborative governance; responsive innovation; sharing economy